The Developmemt of Innovations in Ukrainian Regions: Challenges and Solutions - Nosova, Olga; Makovoz, Oksana (Associacao Nacional de Pos-Graduacao e Pesquisa em Administracao, 2025)
Objective: This study focuses on the role of innovation policy in regional development and examines how innovations contribute to effective regional development in Ukraine. Theoretical Framework: The research is grounded in Schumpeter’s theory of technological accumulation and creative destruction, emphasizing that innovation development provides a solid foundation for understanding the context of the investigation. Method: The methodology employed in this research includes hierarchical cluster analysis to compare 27 Ukrainian regions based on their innovative development. Economic and statistical methods were utilized to assess the level of creative development across these regions, using data from regional statistics on R&D and innovation in Ukraine. Results and Discussion: Hierarchical cluster analysis provides valuable insights into how the classification of regional clusters depends on the input factors of production in Ukrainian regions. The study’s findings confirm the effectiveness of hierarchical cluster analysis in evaluating regional innovation potential. Research Implications: The introduction and implementation of innovation policy aim to reduce inequality and enhance competitiveness among Ukrainian regions. Substantiated the development and implementation of policies considering the innovative components for smoothing regional disparities. It is recommended that regional authorities develop and implement inter-cluster innovative projects and facilitate the exchange of experiences and new ideas. Originality/Value: This study reviews various scientific approaches regarding the role of innovations in regional development. By utilizing hierarchical cluster analysis, the research reveals the asymmetric distribution of input factors of production, suggesting policies that can attract investment to Ukrainian regions. The findings provide valuable insights for researchers, policymakers, and practitioners looking to stimulate innovation for regional development.
O desenvolvimento de inovações nas regiões da Ucrânia: desafios e soluções resumo
Keywords: innovations; development; input factors of production; innovation policy